Prevalence of Hepatitis B Virus Infection in Tanzania: A Systematic Review and Meta-Analysis - Semvua B. Kilonzo; Igembe Nkandala; Ladius Rudovick; Hyasinta M. Jaka; Mariam M. Mirambo; Stephen E. Mshana; Violet D. Kajogoo; Elichilia R. Shao (Journal of Tropical Medicine)
Background and Aim. Hepatitis B virus (HBV) infection represents a significant burden in low-income countries, including Tanzania. The effective planning and implementation of prevention strategies in a country can be hampered by conflicting evidence. To date, no systematic review or meta-analysis has been performed to estimate the burden of disease in a country. The purpose of this review is to summarize and update the available information on the burden of HBV in Tanzania. Methods. We systematically searched the PubMed, Web of Science, African Journals Online, Embase, Cochrane Library, and Google Scholar databases for studies conducted up to March 1, 2023, that estimated the prevalence of HBV in Tanzania based on HBV surface antigen measurements. The DerSimonian–Laird random effects model was used to estimate the overall prevalence of HBV with 95% confidence intervals (CIs). Potential sources of heterogeneity were also investigated. Results. Thirty-one studies with a total sample size of 37,988 were included in the meta-analysis. The overall average HBV prevalence estimate in Tanzania was 6.91% (95% CI = 5.18–8.86%). Subgroup analysis revealed the highest prevalence in the northern zone (9.32%, 95% CI; 2.24–20.36%), among the blood donors (18.72%, 95% CI: 17.43–20.05%) and among the community volunteers (8.76%, 95% CI: 4.55–14.15%). The lowest prevalence was observed in the lake zone at 4.66% (95% CI: 3.49–5.99) and in pregnant women at 4.72% (95% CI: 3.42–6.21). The overall between-study variability showed significant heterogeneity (I2 = 97.41%, P<0.001). Conclusions. Our results showed that Tanzania is a country with moderately high HBV endemicity, with large interregional differences and significantly high numbers of HBV infections within the community. This underscores the need for immediate development of targeted prevention strategies and further epidemiological studies to better understand the pattern of the disease.